Risiko Kegawat - daruratan Kardiovaskuler pada Masyarakat Kawasan Rawa - Wahid, Abdurahman; Agustina, Rismia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
The area of wetland is an area that has limited access to the emergency services ofcardiovascular event and there are several risk factors for cardiovascular emergencies in thecommunity. This study was a descriptive study with cluster random sampling techniques.Participants were 35-49 years old, had no history of stroke, Acute Coronary Syndrome (ACS),cardiac arrest, and diabetes mellitus. Participants was 79 people (male 32, female 47 people)with average age 42.3 years, systolic pressure average 126.8 mmHg, cholesterol level average173 mg / dl, High Density Lipoprotein (HDL) average 40.5 mg/dl, population who smoke are 20(25%), and no one underwent treatment for hypertension. Risk stratification with theFramingham Risk Score showed 19 people (24%) had a high risk ( 5%) of cardiovascularemergency events in the next 10 years